Potential of participatory ergonomic intervention approaches to reduce work-related musculoskeletal disorders among office workers: a review - Albeeli, Ayman (Human Factors and Ergonomics Society Malaysia (HFEM), 2017)
Musculoskeletal disorders (MSDs) are a prevalent issue affecting office workers worldwide and resulting in economic losses and health problems. Pursuing of suitable ergonomic interventions approaches became an inescapable need in order of overcoming the future forecast that expects increased proportion of office-based worker as result of rapid growth of information technology. Participatory ergonomic intervention approaches emerge as a promising ergonomic intervention method to lower the work-related musculoskeletal disorders among office workers. This review underlines the ergonomic intervention methods that have been tried or tested for work-related musculoskeletal disorders reduction in office settings. The current status of using participatory ergonomic intervention approaches has shown potential effectiveness in reducing the prevalence of work-related MSDs. The future perspectives (strengths and opportunities) of these participatory ergonomic intervention approaches includes cost effectiveness, needed materials are simple and effortlessly acquired, and of low-cost. But then, the knowledge gaps (threats and weaknesses) regarding these participatory approaches comprise the lack of quality evaluation studies. Using participatory ergonomic intervention approaches is an imperative component that might help in reducing the prevalence of WMSDs among office-workers in both developed and developing countries and being reliable methods than other sophisticated or high-cost ergonomic intervention methods.